2019
DOI: 10.1590/0103-8478cr20190404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acinetobacter spp. from raw goat Milk

Abstract: Goat’s milk has been suggested as an alternative to cow’s milk, being a better digestible and hypoallergenic option. However, the presence of contaminating bacteria may significantly affect the safety of the product. In this research, we reported the isolation and characterization of Acinetobacter spp. isolates from raw goat milk samples purchased in the state of Rio de Janeiro, Brazil. Twenty-one samples were analyzed and ten isolates of Acinetobacter spp. were obtained. Six were identified as A. guillouiae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
(14 reference statements)
2
7
0
Order By: Relevance
“…Kim et al [32] reported a high prevalence (27.8%) of A. baumannii strains in the raw milk samples of naturally infected animal species with higher resistance toward tetracycline (30.8%), followed by ceftriaxone (4.4%), cefotaxime (12.5%), and gentamicin (2.9%) antimicrobial agents. High prevalence of A. baumannii in different types of milk samples was also previously reported by Vaz-Moreira et al (2011) [33], Gurung et al [34], Saadet al [35], and Ramos and Nascimento [36].A. baumannii and other Acinetobacter species were rarely detected in seafood samples [37][38][39][40].…”
Section: Discussionsupporting
confidence: 73%
“…Kim et al [32] reported a high prevalence (27.8%) of A. baumannii strains in the raw milk samples of naturally infected animal species with higher resistance toward tetracycline (30.8%), followed by ceftriaxone (4.4%), cefotaxime (12.5%), and gentamicin (2.9%) antimicrobial agents. High prevalence of A. baumannii in different types of milk samples was also previously reported by Vaz-Moreira et al (2011) [33], Gurung et al [34], Saadet al [35], and Ramos and Nascimento [36].A. baumannii and other Acinetobacter species were rarely detected in seafood samples [37][38][39][40].…”
Section: Discussionsupporting
confidence: 73%
“…35,36 However, other reports describe the species of Acinetobacter as potential pathogens and are concerned about their detection in foods, including samples of bovine milk, goats and dairy products. [37][38][39] The presence of pathogenic Acinetobacter species in meat for human consumption has been reported by Marí-Almirall and coworkers; 40 although the authors did not find multiresistant strains in their study, they report the risk that this may pose to public health, as these foods may act as potential reservoirs for the spread of Acinetobacter in the human population. Klotz and colleagues, 41 for instance, isolated carbapenem-resistant A. indicus strains in cattle and made an important observation: despite the low pathogenicity of this species, these isolates may contribute to the dissemination of resistance genes to other bacterial species and also to the environment through manure, contributing to the contamination of vegetables used for human consumption.…”
Section: Acinetobacter Spp Relation With Foodmentioning
confidence: 55%
“…Some studies report the presence of Acinetobacter spp. in hospital kitchens and in common food, 39,[43][44][45][46] however the evidence that these microorganisms are foodborne pathogens has not yet been proven. 38,42 Some reports raise suspicions of this transmission.…”
Section: Acinetobacter Spp Relation With Foodmentioning
confidence: 99%
“…E 5,0 x 10 10 3,0 x 10 10 Legend: *The values represent the average of two independent experiments. Sources of isolates: 1 Ramos & Nascimento, 2019;2 Ramos, 2019;3 Bank of bacteria from the Microbiology Laboratory of IFRJ; 4 Ramos & Nascimento, 2020; 5 Oliveira et al, 2012. In developing countries, research and classes involving microorganisms are often not carried out due to the scarcity of resources for the acquisition of the necessary inputs (Uthayasooriyan et al, 2016). The value of conventional culture media, both in agar and in casoy broth, is extremely high because it has complex ingredients.…”
Section: Staphylococcusmentioning
confidence: 99%